Integrated estimation of mathematical knowledge of students at semester time - Aleksandras Krylovas; Juozas Raulynaitis (Lietuvos Matematikos Rinkinys)
The experiment of integrated estimation of students mathematical knowledge at semester time in Vilnius Gediminas Technical University is described.